Salt Reduction in Vegetable Fermentation: Reality or Desire?. Issue 8 (14th June 2013) - Bautista‐Gallego, J.; Rantsiou, K.; Garrido‐Fernández, A.; Cocolin, L.; Arroyo‐López, F. N.
Abstract NaCl is a widely used chemical in food processing which affects sensory characteristics and safety; in fact, its presence is frequently essential for the proper preservation of the products. Because the intake of high contents of sodium is linked to adverse effects on human health, consumers demand foods with low‐sodium content. A 1st step to reduce the use of salt would imply the proper application of this compound, reducing its levels to those technologically necessary. In addition, different chloride salts have been evaluated as replacers for NaCl, but KCl, CaCl2, and ZnCl2 show the most promising perspectives of use. However, prior to any food reformulation, there is a need for exhaustive research before its application at industrial level. Salt reduction may lead to an increased risk in the survival/ growth of pathogens and may also alter food flavor and cause economic losses. This review deals with the technological, microbiological, sensorial, and health aspects of the potential low‐salt and salt‐substituted vegetable products and how this important segment of the food industry is responding to consumer demand.